2012
DOI: 10.3109/14767058.2012.735994
|View full text |Cite
|
Sign up to set email alerts
|

A common problem for neonatal intensive care units: late preterm infants, a prospective study with term controls in a large perinatal center

Abstract: Compared with term infants, late preterm infants are immature physiologically and metabolically, and have higher risks for medical complications such as respiratory distress, hypoglycemia, hyperbilirubinemia, sepsis, feeding difficulty and poor neurodevelopmental outcomes. The incidence of late preterm birth is increasing. We evaluated the clinical and demographic characteristics, short-term outcomes and clinical courses of late preterm infants admitted to our neonatal intensive care unit (NICU). Data from NIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
13

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 25 publications
3
63
0
13
Order By: Relevance
“…The rate of late preterm infants among all preterms was 59.9%. This rate was similar to that of Çelik et al (11), which was 60%. In a study performed in United States, this rate was found to be 71.4% (5).…”
Section: Discussionsupporting
confidence: 78%
“…The rate of late preterm infants among all preterms was 59.9%. This rate was similar to that of Çelik et al (11), which was 60%. In a study performed in United States, this rate was found to be 71.4% (5).…”
Section: Discussionsupporting
confidence: 78%
“…En aquellos pacientes que requirieron ventilación mecánica, fue frecuente encontrar como factores de riesgo el bajo peso al nacer y la edad gestacional temprana 11,12 . En el presente estudio se observó que los infantes con requerimiento de VM tenían un promedio de peso 1882,9 g y de edad gestacional promedio de 32,7 semanas, valores mayores comparados con cifras reportadas en estudios realizados en Latinoamérica, lo que sugiere que en la UCIN de la clínica Universidad de La Sabana ingresan infantes con menor riesgo 11,12 ; cifras que se relacionan con el índice bajo de mortalidad encontrado en los pacientes incluidos dentro del presente estudio comparado con los estudios similares reportados en la literatura [11][12][13] .…”
Section: Discussionunclassified
“…4 In a population-based study, Moster et al 10 [12][13][14] Late preterm infants were repeatedly reported to have more complications and require more NICU admissions secondary to immaturity of their different systems. [15][16][17][18] Endotracheal intubation may or may not be associated with prolonged resuscitation as in many cases it can be related to the presence of meconium stained amniotic fluid. The impact of intubation alone may be hard to tease out especially with the flexibility given in NRP guidelines regarding the timing of the decision when to intubate.…”
Section: Discussionmentioning
confidence: 99%